49. CORRELATES AND PREDICTORS OF HEALTH-RELATED QUALITY OF LIFE IN METASTATIC BRAIN CANCER. (4th August 2020) - Marotta, Dario; Hayward, Emily; Tucker, Zachary; Gerstenecker, Adam; Gammon, Meredith; Mason, Matthew; Willhelm, Gabrielle; Bae, Helen; Triebel, Kristen
Abstract: PURPOSE: Neurocognitive functioning (NCF), mood disturbances, physical functioning, and social support all share a relationship with health-related quality of life (HRQOL). However, a characterization of these relationships in persons with brain metastases (BM) has yet to be identified. METHODS: Ninety-three newly diagnosed persons with BM were administered a cognitive battery to assess neurocognitive functioning, mood disturbances, physical functioning, and social support. The Functional Assessment of Cancer Treatment (FACT) scale was used to measure HRQOL. RESULTS: Mood and physical function correlated with lower HRQOL in every measured domain. Verbal learning and memory correlated with every FACT subscale except emotional quality of life. Social support also correlated with several HRQOL domains. Stepwise linear regressions revealed that mood was the predominate predictor of HRQOL. Social support, physical functioning, verbal learning, and memory also contribute to HRQOL, but to a lesser extent. CONCLUSION: HRQOL is a complex construct affected by mood, physical functioning, and learning and memory. Mood is a domain-independent predictor of HRQOL, while non-mood variables predict HRQOL in domain-specific ways. Thus, multifactorial baseline assessments of persons with BM are encouraged to help mitigate the impact that BM has on HRQOL.